Monitoring the trend of SARS-CoV-2 seroprevalence in Chennai, India, July and October 2020. (14th September 2021) - Kumar, Muthusamy Santhosh; Thangaraj, Jeromie Wesley Vivian; Saravanakumar, V; Selvaraju, Sriram; Kumar, C P Girish; Sabarinathan, R; Jagadeesan, M; Hemalatha, M S; Rani, D Sudha; Jeyakumar, Annadurai; Sonekar, Harshal Bhimrao; Rubeshkumar, Polani; et al.
Abstract: Background: The first serosurvey conducted in Chennai, India in July 2020 reported sudden acute respiratory syndrome coronavirus 2 (SARS-CoV-2) prevalence of 18.4%. The aim of this study was to estimate the seroprevalence in the month of October 2020. Methods: We conducted a survey in 153 streets covering 51 wards and all 15 zones of the city and enrolled from each street 40 individuals ≥10 y of age. We collected 3–5 ml of venous blood and tested for anti-nucleocapsid (N) immunoglobulin (IgG) antibodies using a SARS-CoV-2 IgG assay. We estimated the weighted seroprevalence of SARS-CoV-2 infection and adjusted for test characteristics. Results: Of the 6366 sera tested, 2052 were positive for anti-N IgG antibodies. The weighted seroprevalence after adjusting for test characteristics was 30.1% (95% confidence interval [CI] 24.7 to 36.1). There was wide variation in the seroprevalence between wards, ranging from 11.0% (95% CI 5.6 to 16.4) to 48.1% (95% CI 39.5 to 56.7). Conclusions: The seroprevalence of SARS-CoV-2 infection in Chennai nearly doubled between July and October 2020.